Self-Objectification as A Moderating Variable Between Online Dating Applications Use and The Mental Well–Being Of Filipino Young Adults - Sylvierose Gesmundo (Humanities, Society, and Community, 2023)
Usage of online dating applications increased during the peak of the pandemic, and along with this are the concerns about the mental health of young adults. The study focused on the effects of self-objectification on the relationship between online dating application usage and the mental well-being of its users. A total of 204 participants were gathered from five cities within the bounds of Metro Manila: Quezon City (22%), Manila (44%), San Juan (14%), Mandaluyong (11%), and Caloocan (10%). This study treated the data quantitatively using regression and moderation analysis in Statistical Package for the Social Sciences (SPSS). The findings of the study revealed that there was a moderately negative relationship between online dating applications usage and mental well–being of Filipino young adults (r = -.315; p = .000). This further revealed that frequent usage of online dating applications resulted to lower levels of life and relationship satisfaction, self–esteem, and higher negative affect, body consciousness, and symptoms of eating disorders. However, the study revealed no moderating effect between self-objectification and the relationship between online dating application usage and its users' mental well–being (p = 0.3102). An action plan was proposed to aid online dating application users in dealing with the consequences of too much exposure to the objectifying world of social media in general.